A brief validated screen to identify boys and girls at risk for early marijuana use. (August 2018) - Loeber, Rolf; Clark, Duncan B.; Ahonen, Lia; FitzGerald, Douglas; Trucco, Elisa M.; Zucker, Robert A.
Abstract: To guide recruitment, the ABCD Study requires a method for identifying children at high risk for early-onset substance use that may be utilized during the recruitment process. This study was undertaken to inform the development of a brief screen for identifying youths' risk of early-onset substance use and other adverse outcomes. To be acceptable by participants in this context, consideration of potential items was limited to child characteristics previously determined to be potentially pertinent and parental cigarette smoking. To focus the analyses on a single target substance use outcome pertinent to the stated goals of the ABCD Study, early-onset marijuana use was selected. Utilizing data collected prior to the initiation of the ABCD Study, four longitudinal data sets were used in nine secondary data analyses to test, replicate and validate a brief screening assessment for boys and girls to identify those at risk for early-onset marijuana use by ages 14–15. The combination of child externalizing problems reported by the parent (4 items: destroys things belonging to his/her family or others; disobedience at school; lying or cheating; steals outside the home) and parent smoking (1 item) proved to be the optimal screen. This was largely replicated across the four data sets. Indicators of predictive efficiency were modest in magnitude and statistically significant in 8 out of the 9 analyses. The results informed the screen's optimal threshold for identifying children at risk for early-onset marijuana use. The addition of child internalizing problems did not improve these predictions. Further analyses showed the predictive utility of the screen for several other substance use outcomes at ages 15 to 18, including alcohol and nicotine use. The results support the use of a short screening assessment to identify youth at risk for early-onset substance use in the ABCD Study and other research.